Membangun Jaringan Kerjasama Dalam Rangka Pemberdayaan Perpustakaan - Yuda Aditya; Salsabila Naqiyyah Melfan; Naufal Akbar Halomoan; Alfany Umar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The library is a place of knowledge in which there are many forms of collection, both printed and digital. However, as a forum, it is necessary for the library to strive to meet the needs of its users in terms of providing information, but due to the inability to provide any information needed, it is necessary to collaborate with one library with another library. The research method was carried out using a qualitative method along with a literature study so that several sources were collected that had similar titles with this work. Keyword: network, cooperation, library